(untitled) (Al-Academy, 2023)
Television art is Considerd the first of the audiovisual arts because it is the freest and creative in artistic construction and visual production. He does not seek only entertainment, but he crossed the thresholds of education, spreading awareness and addressing new and innovative topics, through his high ability to address topics that work in both artistic directions in art in its general form, which are (realism) and (impressionism), The artistic dramatic achievement has the ability to achieve the visions and fantasies of the artwork maker by physically representing his artistic image in this high-impact sensory medium. Visual and audio via the TV medium.